Stereodivergent Synthesis of d,d- and l,l-glycero-β-allo-Heptopyranoses on a Dioxanone Scaffold - Palyam, Nagarjuna; Niewczas, Izabella; Majewski, Marek (Synlett, 2012)
We report a stereodivergent synthesis of both enantiomers of glycero-allo-heptose from 2,2-dimethyl-1,3-dioxan-5-one, a readily available nonchiral scaffold, and from two different synthetic equivalents of glyoxal: dimethoxyacetaldehyde and 1,3-dithiane-2-carboxaldehyde. The short synthetic sequence involves first a proline-mediated, and then a lithium enolate mediated aldol reaction at the α- and α′-positions of the dioxanone ring, respectively, and demonstrates the complementary nature of organocatalysis and metal enolate based methods.
Keywords: aldol reaction; organocatalysis; carbohydrates; heterocycles; stereoselective synthesis